18F-Fluorodeoxyglucose PET/CT and dynamic contrast-enhanced MRI as imaging biomarkers in malignant pleural mesothelioma - Hall, DO; Hooper, CE; Searle, J; Darby, M; White, P; Harvey, JE; Braybrooke, JP; Maskell, NA; Masani, V; Lyburn, ID (Lippincott, Williams and Wilkins, 2018)
Purpose The purpose of this study was to compare the use of fluorine-18-fluorodeoxyglucose (18F-FDG) PET with computed tomography (CT) and dynamic contrast-enhanced (DCE) MRI to predict prognosis and monitor treatment in malignant pleural mesothelioma. Patients and methods 18F-FDG PET/CT and DCE-MRI studies carried out as part of the South West Area Mesothelioma Pemetrexed trial were used. 18F-FDG PET/CT and DCE-MRI studies were carried out before treatment, and after two cycles of chemotherapy, on patients treated with pemetrexed and cisplatin. A total of 73 patients were recruited, of whom 65 had PET/CT and DCE-MRI scans. Baseline measurements from 18F-FDG PET/CT (maximum standardized uptake value, metabolic tumour volume and total lesion glycolysis) and DCE-MRI (integrated area under the first 90s of the curve and washout slope) were compared with overall survival (OS) using Kaplan–Meier and Cox regression analyses, and changes in imaging measurements were compared with disease progression. Results PET/CT and DCE-MRI measurements were not correlated with each other. Maximum standardized uptake value, metabolic tumour volume and total lesion glycolysis were significantly related to OS with Cox regression analysis and Kaplan–Meir analysis, and DCE-MRI washout curve shape was significantly related to OS. DCE-MRI curve shape can be combined with 18F-FDG PET/CT to give additional prognostic information. Changes in measurements were not related to progression-free survival. Conclusions 18F-FDG PET/CT and DCE-MRI give prognostic information in malignant pleural mesothelioma. Neither PET/CT nor DCE-MRI is useful for monitoring disease progression.